ROLLING CONTACT FATIGUE PERFORMANCE OF SELECTIVE LASER MELTED TI-6AL-4V - PENG DanHua; ZHANG ZhenWen; ZHANG KaiFei; ZHANG Peng; LI ZhongHua; FU Guang (Jixie qiangdu)
Selective Laser Melting（ SLM） can directly fabricate parts that are difficult or time-consuming for processing or even can not be processed in traditional way. And SLM is one of most promising addictive manufacturing techniques. The current study is mainly concentrated on statics performance,such as tensile and compression properties. However,in many cases,the dynamic performance is required. This research Based on Ti-6 Al-4 V powders as the experimental material,SLM under different post-processing pieces for the rolling contact fatigue performance study. It was found that the roughness and hardness is main factors of rolling contact fatigue performance. Polishing and heat treatment can improve the rolling contact fatigue life. Big roughness causes wear failure of the SLM-fabricated titanium alloy parts,and small roughness mainly leads to spalling failure.